A molecular epidemiological analysis of Burkholderia pseudomallei in southern Thailand. - Jedsada Kaewrakmuk; Sarunyou Chusri; Pacharapong Khrongsee; Soontara Kawila; Vannarat Saechan; Nutjamee Leesahud; Bongkoch Chiewchanyont; Hathairat Thananchai; Kwanjit Duangsonk; Apichai Tuanyok (Public Library of Science (PLoS), 2024)
Melioidosis, a severe bacterial illness caused by Burkholderia pseudomallei, is prevalent in most parts of Thailand, including its southern region situated within the Malay Peninsula. Despite a lower reported incidence rate of melioidosis in the South compared to the Northeast, the mortality rate remains persistently high. This study aimed to better understand the epidemiology and investigate the presence of B. pseudomallei in the natural environment of southern Thailand. Using multi-locus sequence typing (MLST), we characterized B. pseudomallei isolates derived from human cases and compared them with previously reported sequence types (STs) from the same region. A total of 263 clinical isolates retrieved from 156 melioidosis patients between 2014 and 2020 were analyzed, revealing 72 distinct STs, with 25 (35%) matching STs from Finkelstein's environmental isolates collected in southern Thailand during 1964-1967. Notably, strains bearing STs 288, 84, 54, 289, and 46 were frequently found among patients. Additionally, we observed strain diversity with multiple STs in 13 of 59 patients, indicating exposure to various B. pseudomallei genotypes in the environmental sources of the infection. Environmental surveys were conducted in Songkhla Province to detect B. pseudomallei in soil and water samples where local patients lived. Of the 2737 soil samples from 208 locations and 244 water samples from diverse sources, 52 (25%) soil sampling locations and 63 (26%) water sources were cultured positive for B. pseudomallei. Positive soil samples were predominantly found in animal farming area and non-agricultural zones like mountains and grasslands, while water samples were frequently positive in waterfalls, streams, and surface runoffs, with only 9% of rice paddies testing positive. Collectively, a significant proportion of recent melioidosis cases in Songkhla Province can be attributed to known B. pseudomallei STs persisting in the environment for at least the past six decades. Further characterization of B. pseudomallei isolates from recent environment surveys is warranted. These findings illuminate the contemporary landscape of B. pseudomallei infections and their environmental prevalence in southern Thailand, contributing to the regional threat assessment in Thailand and Southeast Asia.